(untitled) (Lapai Journal of Economics, 2022)
This study examined the impact of global factors on manufacturing output growth in Sub-Saharan Africa. The study used annual panel data of forty (40) Sub-Sahara African countries from 1981 to 2019, constituting 38 observations for each country. The study employed secondary data obtained from World Bank’s World Development Indicators. The dynamic panel autoregressive distributed lag (PARDL) model was used through the pooled mean group (PMG), mean group (MG) and dynamic fixed effects (DFE) estimators. The findings of the study revealed that the only global factor that have significant impact on manufacturing output growth in Sub-Saharan Africa was foreign direct investment, which has a positive impact. The study concluded that, the inflow of foreign investment is vital to boosting manufacturing output in SSA countries. It therefore, recommended that policymakers in these countries should make efforts to attract further inflows of foreign capitals by ensuring a stable and business friendly economic environment through their macroeconomic policies of maintaining a low level of inflation and developing business-enhancing infrastructures.